LOOKING IN THE n-DIMENSIONAL SPACE - Jamroz, Dariusz (Computer Science, 2020)
The possibility of looking at the cxterior appearancc of the n-dimensional solids using the cyc- sight is introduccd in this article. The dcvcloped mathematical model allows to creatc the Com puter program that makes looking at any solid having any number of dimensions possible. The appearancc of hypothetical solids from various perspectives is shown as well, for instance the four-dimcnsional and the seven-dimensional dices which are the multidimensional equivalents of a cubc.